Technology Integration in Learning: Understanding of Life Value by Students in MARS Film - Cholimah, Nur; Arifiyanti, Nurul; Maharani, Oktaviana; Agustiningsih, Rini (Informasi, 2024)
The integration of technology in learning through film can increase students understanding of life values, which will be important for an educator. This paper aims to describe the understanding of life value by students in the MARS Film. It is quantitative research with an open survey method. Researchers distributed questionnaires to 93 students and used descriptive analysis. The results showed the value of life that the students can find in the film are hard work and fighting spirit. As parents, the value of life that can be learned is to support dreams by providing the best education and motivation. It also found that moral values can be learned is persistence and respect. This Film is recommended for learning because it can inspire and motivate the importance of education.